Pulse Drip Irrigation Improves Yield, Physiological Responses, and Water-Use Efficiency of Sugarcane - de Menezes, Sirleide Maria; da Silva, Gerônimo Ferreira; da Silva, Manassés Mesquita; de Oliveira Filho, Ronaldo Alves; Jardim, Alexandre Maniçoba da Rosa Ferraz [UNESP]; Silva, José Raliuson Inácio; Silva, Ênio Farias de França e; Silva, José Vieira; dos Santos, Márcio Aurélio Lins (Springer Nature, 2024)
Pulsed drip irrigation helps irrigation management in the search for sustainability and water rationalization in irrigated cropping systems, becoming an effective tool in mitigating stress due to water deficit. Therefore, the present research aimed to evaluate photosynthesis, gas exchange, leaf area, and biomass production of sugarcane under irrigation depths applied by pulsed and continuous drip. For this, we conducted a field experiment from December 2020 to December 2021. The plants were subjected to two types of irrigation applications (pulsed and continuous) and five irrigation depths (40, 60, 80, 100, and 120% of crop evapotranspiration (ETc)). Four pulses were defined for the pulse irrigation type with a fixed interval of 40 min of rest between two applications. Gas exchange, water-use efficiency, leaf area, and sugarcane biomass yield were evaluated. Based on the results, increased water stress reduced gas exchange, leaf area, and fresh biomass production of sugarcane. Pulsed irrigation increased photosynthesis (21%), water-use efficiency (17%), and leaf area (39%). The fresh biomass production of the stem (147 Mg ha−1) and leaves (12 Mg ha−1) was increased when irrigation was performed in a pulsed manner. Principal component analysis suggested pulsed irrigation with 80% of ETc as the treatment that provided the best physiological indices and fresh biomass production in sugarcane.
Keywords: Biomass; PCA; Saccharum officinarum; Water deficit